How to age - Karpf, Anne, ....- (London : Macmillan, 2014)
Society has a deep fear of ageing. Old age is increasingly viewed as a biomedical problem, something to be avoided at all costs and then vanished away by medicine. Anne Karpf urges us to change our narrative. Exploring how our outlook on ageing is historically determined and culturally defined, she draws upon case studies, old and new, to suggest how ageing can be an actively enriching time of immense growth. She argues that if we can recognize growing older as an inevitable part of the human condition, then the great challenge of ageing turns out to be none other than the challenge of living.
Keywords: Ouderen ; psychologie